Comparative pathogenicity of different subtypes of duck hepatitis A virus in Pekin ducklings - Liu, Rongchang; Shi, Shaohua; Huang, Yu; Chen, Zhen; Chen, Cuiteng; Cheng, Longfei; Fu, Guanghua; Chen, Hongmei; Wan, Chunhe; Fu, Qiuling (Veterinary microbiology, 2019)
•DHAV-1a caused pancreatic bleeding or yellowing, and spleen swelling and bleeding of infected ducklings, but with no opisthotonos clinical signs.•Pathogenicity of DHAV-1a is significantly different than that of classical DHAV (DHAV-1 and DHAV-3).•There was no significant difference in pathogenicity of DHAV-3 (G) and DHAV-1 (FZ86) strains in mainland China. Duck hepatitis A virus (DHAV) is a major pathogen of viral hepatitis in ducks, which is a fatal and contagious disease of young ducklings. Despite the identification of numerous DHAV strains (e.g. DHAV-3, DHAV-2, DHAV-1 and DHAV-1a), the pathogenic differences among the different subtypes have not been evaluated. The objective of this study was to compare the pathogenic properties of three epidemic strains DHAV-3, DHAV-1, and DHAV-1a in mainland China, in a Pekin duckling infection model. We evaluated the pathogenicity of these different subtypes by investigating clinical signs, macroscopic and microscopic lesions, immunohistochemical examination, and viral RNA detection after experimental inoculation of Pekin ducklings with the three different DHAV strains. There was no significant difference in pathogenicity between DHAV-3 and DHAV-1. Pathogenicity of DHAV-1a differed significantly from that of classical duck hepatitis A (DHAV-3 or DHAV-1), in that there were no clinical signs of opisthotonos. More importantly, pancreatic bleeding or yellowing, and spleen swelling and bleeding were the predominant lesions in the DHAV-1a group, while liver and spleen lesions were the main signs in classical hepatitis (DHAV-1/3). Our findings indicate that there are differences in the pathogenicity of different subtypes of DHAV in ducklings, which may be useful for understanding the biological characteristics of the different subtypes of DHAV in ducks.